2013
DOI: 10.1021/nl401420s
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Block Copolymer Photovoltaics with near 3% Efficiency through Microphase Separation

Abstract: Organic electronic materials have the potential to impact almost every aspect of modern life including how we access information, light our homes, and power personal electronics. Nevertheless, weak intermolecular interactions and disorder at junctions of different organic materials limit the performance and stability of organic interfaces and hence the applicability of organic semiconductors to electronic devices. Here, we demonstrate control of donor-acceptor heterojunctions through microphase-separated conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
303
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(314 citation statements)
references
References 66 publications
9
303
1
1
Order By: Relevance
“…The highest performing example of this strategy to date achieved a power conversion efficiency of 3.1% employing poly(3-hexylthiophene) (P3HT) as the donor material and poly(2,7-(9′,9′-dioctylfluorene)-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole) (PFTBT) as the acceptor material in the BCP P3HT-b-PFTBT (Figure 2a, R = H). 13 The authors observed phase separation into 9 nm domains in this system, which may have contributed to the high performance. However, in a subsequent investigation of 30 closely related P3HT-b-PFTBT BCP derivatives, little or no phase separation was obtained regardless of processing conditions.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The highest performing example of this strategy to date achieved a power conversion efficiency of 3.1% employing poly(3-hexylthiophene) (P3HT) as the donor material and poly(2,7-(9′,9′-dioctylfluorene)-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole) (PFTBT) as the acceptor material in the BCP P3HT-b-PFTBT (Figure 2a, R = H). 13 The authors observed phase separation into 9 nm domains in this system, which may have contributed to the high performance. However, in a subsequent investigation of 30 closely related P3HT-b-PFTBT BCP derivatives, little or no phase separation was obtained regardless of processing conditions.…”
Section: Introductionmentioning
confidence: 79%
“…However, in these blended materials, the choice of solvent is restricted to those that can accommodate both components to some threshold level. To date, this most often dictates the use of chlorinated and toxic solvents that are disadvantageous for industrial applications, 13 although there have been recent advances in the use of non-chlorinated aromatic solvents such as mesitylene and anisole. 14,15 One alternative to this blending approach is the covalent linkage of donor and acceptor material into a single entity.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these remarkable performances, the realization of solution-processed BHJ solar cells still poses a number of problems related to both the nature of the active materials and the fabrication process [11]. For example, the finecontrol of phase separation and achieving high chargecarrier mobility in active layers are still very difficult with BHJ solar cells [ As another interesting strategy, electron donoracceptor dyad, triad, multiad and block copolymer molecules or all-in-one molecules where the electron donor (D) and acceptor (A) units are covalently linked in a single molecule have been reported for their potential as photovoltaic materials [12,[14][15][16][17][18][19]. These single-component photovoltaic materials possess multifunctions such as light harvesting, exciton dissociation and electron and hole transport.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several major advantages, such as a considerable simplification of device fabrication, stabilization of the morphology of the active material, and efficient (or fast) charge separation can be expected in the single-component OSCs [11]. At present, the PCE for single-component OSCs has surpassed 2% [12,15,17], which is lower than that of BHJ solar cells. This is because the design of electron donor-acceptor molecules for efficient single-component OSCs is in fact difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The covalent interactions can be effectively tapped to form block copolymers (BCPs) which has numerous applications such as, an etch mask for nano/meso scale patterning, photovoltaic devices, drug delivery, etc [1][2][3][4][5][6]. Apart from the cited applications, BCPs are also being explored for their applicability as photonic materials [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%